Characteristics of Lung Cancer Patients at Dr. Soedarso Hospital Pontianak from 2017 to 2019 - Agusriani Putri; Sari Eka Pratiwi; Risa Febriana Musawaris (Indonesian Journal of Cancer, 2023)
Background: Lung cancer is the second most commonly diagnosed malignancy and the leading cause of death in 2020. Preliminary studies from 2014 to 2019 at Dr. Soedarso Hospital Pontianak showed there was an increase in lung cancer cases. This study aimed to determine the clinical profile of patients with lung cancer in Dr. Soedarso HospitalMethods: This epidemiological study used medical records from patients diagnosed with lung cancer at Dr. Soedarso Hospital Pontianak from 2017 to 2019. It was a cross-sectional study, and 81 samples met the criteria. The inclusion criteria are the completeness of data and the results of cytopathology laboratory examinations. The data were processed using Microsoft Excel.Results: In this study, based on the characteristics of patients diagnosed with lung cancer in Dr. Soedarso Hospital, 82.7% are male with an average diagnosed age of 54.8 years, and 72.8% of patients do not have a smoking history. The common symptoms of patients are shortness of breath (77.8%), chest pain (55.6%), and weight loss (30.9%). The most common type is Non-Small Cell Lung Carcinoma (NSCLC) specifically Adenocarcinoma (76.5%).Conclusion: This study shows that lung cancer incidence in males was higher than in females, and most patients diagnosed did not have a smoking history. The most common symptom of patients is shortness of breath with the most common type of cytopathology results being adenocarcinoma.